Porcelain Heart: A Case of Diffuse Myocardial Calcification - Hu, Jiun-Yiing (Radiol Cardiothorac Imaging, 2020)
The pathophysiology of myocardial calcifications is variable and may have potentially fatal consequences if undiagnosed and untreated.